Effect of phonetic speech training on the pronunciation of vowels in a foreign language - Mildner, Vesna (Array, 2007)
The paper presents the results of speech training exercises on a sample of American English and Spanish native speakers learning Croatian as a foreign language. The success of training was assessed by a panel of trained phoneticians, who evaluated examples of speech before and after a series of individual training sessions. Two different evaluation tests revealed significant improvement in the quality of pronunciation of the five Croatian wovels, which was also reflected in the shape of their vowel space expressed in terms of F1 and F2 frequencies.